PERILAKU KOMUNIKASI MASYARAKAT ADAT DALAM MENOLAK RENCANA REKLAMASI TELUK BENOA - Desak Gede Karlina Satwiva Wijaya; Dwi Retno Hapsari; Rilus A Kinseng (Universitas Djuanda Bogor, 2023)
The Benoa Bay reclamation idea is an interesting isssue due to presidential regulation 51 of 2014 has not been revised. This condition effects in the struggle of indigenous peoples be going to start continuesly from the difference of interests between indigenous peoples and the government which ultimately produced a social movements. The social movement has occured in a long period of time since 2012 to 2019. The influence of traditional power can contribute to delaying the progress of the reclamation project. This research aims to examine the communication patterns exhibited by the local community and Balinese customs in their opposition to the Benoa Bay reclamation project. The study adopts an ethnographic approach using qualitative techniques as the research methodology. Data collection involves gathering primary and secondary data through interviews and literature review. The research is conducted in Kedonganan Adat Village, located in Kuta District, Badung Regency. The findings reveal that the Kedonganan indigenous people express their rejection of the Benoa Bay reclamation project through meaningful messages conveyed both verbally and nonverbally. The communication primarily occurs through interpersonal interactions to ensure better comprehension of the messages. These messages carry symbolic significance and have given rise to a subtle social movement, believed to provide protection by the Kedonganan community. Consequently, the Kedonganan indigenous people have successfully secured their victory in the opposition against the Benoa Bay reclamation project through the utilization of customary power and cultural strength.